2007
DOI: 10.1002/cncr.22762
|View full text |Cite
|
Sign up to set email alerts
|

Resection alone in 58 children with limited stage, lymphocyte‐predominant Hodgkin lymphoma–experience from the European network group on pediatric Hodgkin lymphoma

Abstract: BACKGROUND. Lymphocyte‐predominant Hodgkin lymphoma (LPHL) is a rare, CD20‐positive, good prognostic lymphoma in children. Patients with early‐stage LPHL who underwent successful surgical lymph node resection alone have been reported. To clarify the optimum treatment strategy in children, European study groups were asked to report their experience of surgery alone used in the treatment of pediatric LPHL. METHODS. Data from 58 patients were collected by the French Society for Pediatric Cancers, the German‐Austr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
60
1
7

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(74 citation statements)
references
References 30 publications
(46 reference statements)
6
60
1
7
Order By: Relevance
“…10 Our results show that initiating treatment at the time of diagnosis may improve PFS, compared with watchful waiting, which was the most frequent initial management and concerned more than one-third of our patients. Based on pediatric series, 11,12 the EuroNet-PHL-LP1 study recommends a follow-up without further treatment in children and adolescents with stage IA disease, and complete resection of involved lymph nodes. However, in our study, even after complete surgical resection of local lesions, additional treatment improved PFS compared to watchful waiting.…”
Section: Discussionmentioning
confidence: 99%
“…10 Our results show that initiating treatment at the time of diagnosis may improve PFS, compared with watchful waiting, which was the most frequent initial management and concerned more than one-third of our patients. Based on pediatric series, 11,12 the EuroNet-PHL-LP1 study recommends a follow-up without further treatment in children and adolescents with stage IA disease, and complete resection of involved lymph nodes. However, in our study, even after complete surgical resection of local lesions, additional treatment improved PFS compared to watchful waiting.…”
Section: Discussionmentioning
confidence: 99%
“…19 Single-agent rituximab has also been explored; but despite a high response rate, it is likewise associated with a high rate of relapse, possibly including transformation to large cell lymphoma. [20][21][22] From these analyses, it appears unlikely that rituximab alone is curative.…”
Section: Discussionmentioning
confidence: 99%
“…We note that the numbers managed by observation alone are too small to demonstrate statistical significance, but our outcomes are in agreement with other studies suggesting that management by resection only may be appropriate in selected groups of limited stage patients. 20 The majority of patients were able to be treated by involved-field radiotherapy (IFRT) alone, avoiding many of the toxicities of extended field radiotherapy or chemotherapy. Previous published studies have suggested that for early stage patients, radiotherapy alone may be potentially curative.…”
Section: Discussionmentioning
confidence: 99%